Physico-chemical characteristics and fatty acid profile of allium fistulosum vegetable plant - Adeyeye, Adeniyi (International Journal of Advanced Chemistry, 2020)
The physicochemical properties of the plant and the fatty acid profile of the plant oil of Allium fistulosum have been determined using standard methods of the AOAC. The proximate composition gave moisture content of 89.55%, ash content 0.82%, crude oil 0.64%, crude protein 1.82%, crude fibre 1.65% and carbohydrate 5.54%. The most abundant fatty acids in decreasing order of abundance were linoleic (52.87%) > oleic (17.57%) > palmitic (9.80%) > stearic (8.81%) > linolenic (2.88%) > palmitoleic (2.84%) > myristic (1.28%) > behenic (1.23%). Others with concentrations less than 1.00% are lauric, arachidonic, behenic and lignoceric acids. Linoleic and oleic acids were the most abundant of the total fatty acids and also of the total unsaturated fatty acids with the two totaling 70.44% of all fatty acids. Palmitic and stearic acids were the two most abundant saturated fatty acids, totaling 18.61% of all fatty acids. The total unsaturated fatty acids (77.35%) predominated the total saturated (22.63%), while the percentage poly-unsaturated (56.34%) was far greater than mono-unsaturated (21.04%). The high level of essential fatty acids in the plant oil is an advantage in food consumption and the good total unsaturated/saturated (PS) ratio makes the fruit oil nutritionally very useful to be adopted for domestic purposes.